2018
DOI: 10.1007/s11214-018-0521-6
|View full text |Cite
|
Sign up to set email alerts
|

The OSIRIS-REx Spacecraft and the Touch-and-Go Sample Acquisition Mechanism (TAGSAM)

Abstract: The Origins, Spectral-Interpretation, Resource-Identification, Security and Regolith-Explorer (OSIRIS-REx) spacecraft supports all aspects of the mission science objectives, from extensive remote sensing at the asteroid Bennu, to sample collection and return to Earth. In general, the success of planetary missions requires the collection, return, and analysis of data, which in turn depends on the successful operation of instruments and the host spacecraft. In the case of OSIRIS-REx, a sample-return mission, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 20 publications
0
60
0
Order By: Relevance
“…These locations may be reservoirs for smaller particles produced or exposed during the crater formation process, while boulder fracturing processes or abrasion/mechanical erosion between boulders could both contribute to the production of fine grains more widely across the surface of Bennu. The evidence for finegrained material (of the centimeter-scale sizes that are ingestible by the OSIRIS-REx sample mechanism [Bierhaus et al 2018] and of smaller, micron-scale sizes) is abundant despite not being resolved with current imaging. The measured thermal inertia suggests a substantial population of centimeter-sized particles (DellaGuistina and Emery et al 2019).…”
mentioning
confidence: 99%
“…These locations may be reservoirs for smaller particles produced or exposed during the crater formation process, while boulder fracturing processes or abrasion/mechanical erosion between boulders could both contribute to the production of fine grains more widely across the surface of Bennu. The evidence for finegrained material (of the centimeter-scale sizes that are ingestible by the OSIRIS-REx sample mechanism [Bierhaus et al 2018] and of smaller, micron-scale sizes) is abundant despite not being resolved with current imaging. The measured thermal inertia suggests a substantial population of centimeter-sized particles (DellaGuistina and Emery et al 2019).…”
mentioning
confidence: 99%
“…Following the delivery of the Flight instrument to the spacecraft developer and flight system integrator, Lockheed Martin Space Systems (LMSS; Bierhaus et al 2017), three noise sources were observed during spacecraft testing. The first consisted of extremely high noise on the IR signal that occurred without any degradation in the servo performance.…”
Section: Post-delivery Testingmentioning
confidence: 99%
“…The OSIRIS-REx spacecraft will collect surface regolith via a touch-and-go sample acquisition mechanism (TAGSAM) that fluidizes loose particles with high-pressure, high-purity N 2 /He gas (Bierhaus et al 2017). The N 2 /He gas carries the samples into a cylindrical sample container, enclosed by biaxially oriented polyethylene terephthalate (e.g., Mylar®) flaps; 5% He is added for leak checking prior to launch.…”
Section: Introductionmentioning
confidence: 99%